A study on tilted tunnel fire under natural ventilation. (April 2016) - Chow, W.K.; Gao, Y.; Zhao, J.H.; Dang, J.F.; Chow, Nadia C.L.
Abstract: Tilted tunnel fire under natural ventilation has been discussed. Smoke movement in a scale tunnel model of length 8 m, width 1.5 m and height 1 m was studied. Air temperature distribution and velocity components along the longitudinal axis at the tunnel opening were measured. Simulations using Computational Fluid Dynamics on smoke movement in the tilted tunnel fire were then carried out. Buoyancy of smoke layer in the tilted tunnel model was deduced by integrating experimental data with simulations results. Smoke velocity distributions in different tilted tunnels were studied numerically. For a horizontal tunnel, the smoke temperature decay rate along the longitudinal direction can be described by an exponential function. For tunnels tilted from 3° to 9°, smoke temperature decayed with different exponential functions on the two sides of the fire. The smoke velocity along the longitudinal axis was not symmetric about the fire source, but with a maximum value located on the leeward side in tunnels tilted at 3–9°. The neutral plane of flow disappeared at the lower opening of the tunnel when the angle was above 9°. Empirical expressions of smoke temperature and velocity decays along the longitudinal axis for a tilted tunnel were also derived. Highlights: Smoke movement, temperature and velocity in a scale tunnel model were studied. CFD simulations on smoke movement in the tilted tunnel fire were then carried out. Smoke temperature decay rate in horizontal tunnels is symmetrical on both sides. Smoke temperature in tilted tunnels decayed with different exponential functions. Smoke velocity along the longitudinal axis in tilted tunnels was not symmetrical.